Disease recurrence in localized scleroderma: a retrospective analysis of 344 patients with paediatric‐ or adult‐onset disease. (1st March 2015) - Mertens, J.S.; Seyger, M.M.B.; Kievit, W.; Hoppenreijs, E.P.A.H.; Jansen, T.L.Th.A.; van de Kerkhof, P.C.M.; Radstake, T.R.D.; de Jong, E.M.G.J.
Summary: Background: Localized scleroderma (LoS) is characterized by a phase of disease activity followed by remission. However, disease recurrences occur. Knowledge concerning these recurrences can help prompt treatment, thereby preventing disease damage. Objectives: To investigate the frequency and characteristics of disease recurrences in paediatric‐ and adult‐onset LoS, and to identify patient variables that are associated with a higher risk of disease recurrence. Methods: Retrospective chart reviews were performed of patients with LoS. Data concerning the frequency and characteristics of the disease recurrences were collected. A multivariate analysis was performed to identify patient variables that were associated with a higher risk of disease recurrence. Results: In total, 344 patients were included in the analysis, of whom 119 (35%) had paediatric‐onset LoS and 225 (65%) had adult‐onset LoS. Disease recurrence was present in 27% ( n = 32) of the paediatric‐onset group and 17% ( n = 39) of the adult‐onset group ( P = 0·037). Multivariate analysis identified a statistically significant association between disease recurrence and the linear LoS of the limbs subtype, independent of age at disease onset. Conclusions: Recurrences in LoS occurred in almost one‐quarter of the patients and were most frequent in the linear LoS of the limbs subtype, independent of age at disease onset. These disease recurrences can occur even after many years of quiescent disease. Awareness of the high recurrence rates may help treating physicians to recognize reactivation of the disease, leading to a decreased delay in treatment reinitiation.